Inclusion of a core patient-reported outcomes battery in adolescent and young adult cancer clinical trials. (21st October 2022) - Roth, Michael E; Parsons, Susan K; Ganz, Patricia A; Wagner, Lynne I; Hinds, Pamela S; Alexander, Sarah; Bingen, Kristin; Bober, Sharon L; Brackett, Julienne; Cella, David; Henry, N Lynn; Indelicato, Daniel J; et al.
Abstract: Disparities in care, treatment-related toxicity and health-related quality of life (HRQoL) for adolescents and young adults (AYAs, aged 15-39 years) with cancer are under-addressed partly because of limited collection of patient-reported outcomes (PROs) in cancer clinical trials (CCTs). The AYA years include key developmental milestones distinct from younger and older patients, and cancer interrupts attainment of critical life goals. Lack of consensus on a standardized approach to assess HRQoL and treatment-related toxicity in AYA CCTs has limited the ability to improve patient outcomes. The National Cancer Institute's Clinical Trials Network AYA PRO Task Force was assembled to reach consensus on a core set of PROs and foster its integration into AYA CCTs. Eight key considerations for selecting the core PRO AYA battery components were identified: relevance to AYAs; importance of constructs across the age continuum; prioritization of validated measures; availability of measures without licensing fees; availability in multiple languages; applicability to different cancer types and treatments; ability to measure different HRQoL domains and toxicities; and minimized burden on patients and sites. The Task Force used a modified Delphi approach to identify key components of the PRO battery. The Patient-Reported Outcomes Measurement Information System (PROMIS) and the PRO Common Terminology Criteria for Adverse Events Measurement System met all criteria and were selected to assess HRQoL and treatment toxicity, respectively. Investigators are rapidly incorporating the recommendations of the Task Force into AYA trials. Inclusion of a standardized assessment of HRQoL and treatment toxicities in AYA CCTs is a vital first step to develop interventions to improve health outcomes for AYAs diagnosed with cancer.